Probable Association of Hearing Loss, Hypertension and Diabetes Mellitus in the Elderly - Meneses-Barriviera, Caroline Luiz; Bazoni, Jéssica Aparecida; Doi, Marcelo Yugi; Marchiori, Luciana Lozza de Moraes (International Archives of Otorhinolaryngology, 2018)
Introduction The aging process causes changes in body structure in a continuous manner, and contributes to clinical disorders. Life expectancy is increasing, especially in developing countries.Objective To assess the prevalence of hearing loss and its possible association with hypertension and diabetes mellitus (DM) in the elderly.Methods A cross-sectional study with 519 elderly individuals aged over 60 years who underwent an audiological evaluation (pure tone audiometry), and answered a comorbidity questionnaire that included questions about age, gender, tinnitus and medical history, with data concerning DM. The dependent variable was the presence of hearing loss. The independent variables were age, gender, DM and hypertension. The variables were presented in absolute numbers and proportions, and enabled us to estimate the prevalence. The statistical analysis was performed through multiple logistic regression with 95% confidence intervals and values of p < 0.05 for the hearing loss and its associated factors.Results A total of 519 subjects of both genders with a median age of 69 years were evaluated, and the individuals who did not attend the audiometric test were excluded from the study, so the final sample was composed of 498 subjects. Sensorineural hearing loss was more prevalent (66.26%) of most frequently with bilateral hearing loss of 91.56% and 26.50% with mild degree. The statistical analysis showed that the variable DM was associated with the high frequency of hearing loss in the elderly, and according to the multiple logistic regression, the risk factors are independent of the hearing loss only for age and exposure to occupational noise.Conclusions There was a statistically significant difference between hearing loss at high frequencies and the risk factors, that is, age and DM.
Keywords: hearing loss; hypertension; diabetes